THE ANALYSIS OF SCIENCE TEACHER QUESTIONING SKILLS IN JUNIOR HIGH SCHOOL IN DELI SERDANG DISTRICT - Sari, Nurhaty Purnama (JURNAL DIMENSI, 2013)
A descriptive research that aims to describe: (1) the level of teacher questions based on gender and teaching experience; (2) students’ response to the level of teacher question; (3) teacher’s ability to apply basic and advance questioning skills based on gender and teaching experience has been implemented in Junior High School. About 20 science teachers who teach in 8th grade of Junior High School come from 9 schools have been involved this study. Data were collected through observation and questionnary. The results showed that Junior High School science teacher mostly used low-level cognitive questions (85,8%). A few of other used high-level cognitive questions (14,2%). There was no difference even gender and teaching experience. In level questions, teacher mostly asked about structure (42,80%) and organ (34,20%). A few of other asked about mechanism (18,40%) and desease (18,40%) in circulatory system chapter. Mostly students' response to the level of teacher questions were simultaneous (93.88%), with scientific answer was very low category (39,80%). In basic skills components, teacher mostly used spread with very low category (10%). In advanced questioning skills components have changed the level of cognitive demand (35%), usage tracking questions with various techniques (15%), and improving the interaction (50%) were very low category. There were no differences basic and advanced asking skills even gender and teaching experience.